2004
DOI: 10.1530/eje.0.1510309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of octreotide on sleep apnoea and tongue volume (magnetic resonance imaging) in patients with acromegaly

Abstract: Objectives: Sleep apnoea has been consistently reported to occur in acromegaly. Both obstructive apnoeas, in which apnoeas are due to intermittent obstruction of the upper airways, as well as central apnoeas are known to occur. Because the relationship between disease activity and severity of sleep apnoea is currently unclear, we have performed a prospective study to address this issue. Design and methods: In 14 newly diagnosed patients with active acromegaly (eight females and six males; mean age 57^4 years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 34 publications
(33 reference statements)
6
54
0
10
Order By: Relevance
“…In this series of patients with active acromegaly, we found an SA prevalence of 87.5% and an SAS prevalence of 75%, confirming previous reports from others studies (6,17,18). Only one patient (4.7%) had the central form of SA that was related to a severe left ventricular dysfunction and Cheyne-Stokes breathing episodes at PSG.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this series of patients with active acromegaly, we found an SA prevalence of 87.5% and an SAS prevalence of 75%, confirming previous reports from others studies (6,17,18). Only one patient (4.7%) had the central form of SA that was related to a severe left ventricular dysfunction and Cheyne-Stokes breathing episodes at PSG.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies suggested that upper airway narrowing caused by changes in pharyngeal soft tissues may play a more relevant role in the development of OSA in acromegalic patients than skeletal anomalies (19,22,23). In addition to adenoid, uvular, and tonsilar hypertrophy, macroglossia also narrows pharyngeal airway space (18). MRI, compared with other imaging techniques, has the advantage of more precise delineation of soft tissue and determination of length and thickness of soft palate and tongue (18), which is why this method was adopted in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations